Ownership structure and earnings management: the role of environmental sustainability as moderator variable. A Further analysis. Saudi evidence - Al-Matari, Ebrahim Mohammed (Cogent business & management, 2025)
This study aims to examine the connection between ownership structure and earnings management, as well as explore how environmental sustainability influences this relationship. The research analyzes data from 917 companies, gathered from annual reports, Bloomberg, and DataStream. OLS regression is utilized to assess direct and indirect links between ownership structure and earnings management. The study also employs robustness and sensitivity tests to evaluate indirect relationships among ownership structure, environmental sustainability, and earnings management. Results from fixed regression align with the primary test findings. The research reveals a negative association between Foreign Ownership and earnings management. Although Government Ownership (GOOW), Institutional Ownership (INOW), Family Ownership (FMOW), and Environmental Sustainability (ES) show negative correlations with earnings management, these relationships lack statistical significance. The study also uncovers a slight negative impact of environmental sustainability on the connection between Foreign Ownership (FOROW) and Institutional Ownership (INOW) with earnings management. Supplementary tests corroborate the primary results. This work addresses a gap in current literature and creates opportunities for further in-depth research on the subject. To confirm the results, robustness tests are undertaken, such as endogeneity checks with fixed effect model and two-stage least squares (2SLS). The findings serve as a warning to policymakers, entrepreneurs, stakeholders, and researchers about the significance of ownership structure characteristics that may impede its success.